Creative use of instructional media in elementary Informatics learning - Aam Trianawati (Hipkin Journal of Educational Research, 2026)
The advancement of digital technology demands that primary schools equip students with digital literacy skills from an early age. This study was conducted to explore the implementation of the Kurikulum Merdeka in the Informatics subject at SD Laboratorium UPI, a model school with ideal facilities and instructional practices. This research is significant because laboratory schools also face challenges similar to those of regular public schools, making them a realistic reflection of actual field conditions. Using a qualitative case study approach, data were collected through semi-structured interviews with the Informatics teacher and document analysis. The findings reveal that, despite limitations in the technological infrastructure, the teacher was able to deliver engaging, contextually relevant learning by using available tools, including the supervised use of students’ personal devices. Informatics is positioned as a formal subject, reflecting the school’s commitment to strengthening students’ digital competencies from an early stage. The study identifies both supporting and inhibiting factors in learning, such as access to media, teacher readiness, and student characteristics. These findings offer practical recommendations for primary schools with either complete or limited facilities to implement meaningful and adaptive Informatics education.   Abstrak Perkembangan teknologi digital menuntut sekolah dasar untuk membekali murid dengan literasi digital sejak dini. Penelitian ini dilakukan untuk mengeksplorasi implementasi Kurikulum Merdeka pada mata pelajaran Informatika di SD Laboratorium UPI, sebuah sekolah model yang diasumsikan memiliki fasilitas dan praktik pembelajaran ideal. Penelitian ini penting dilakukan karena sekolah laboratorium juga menghadapi tantangan yang serupa dengan sekolah umum, sehingga dapat menjadi cerminan kondisi riil di lapangan. Menggunakan pendekatan studi kasus kualitatif, data dikumpulkan melalui wawancara semi-terstruktur dengan guru Informatika dan analisis dokumen. Hasil penelitian menunjukkan bahwa, meskipun terdapat keterbatasan infrastruktur teknologi, guru mampu melaksanakan pembelajaran yang menyenangkan dan kontekstual dengan memanfaatkan perangkat yang tersedia, termasuk penggunaan perangkat pribadi murid di bawah pengawasan. Informatika diposisikan sebagai pelajaran formal, mencerminkan komitmen sekolah terhadap penguatan kompetensi digital sejak dini. Penelitian ini mengidentifikasi faktor pendukung dan penghambat pembelajaran seperti media, kesiapan guru, dan karakteristik murid. Temuan ini memberikan rekomendasi praktis bagi sekolah dasar, baik yang memiliki fasilitas lengkap maupun yang terbatas, dalam mengimplementasikan pendidikan Informatika yang bermakna dan adaptif. Kata Kunci: kreativitas guru; Kurikulum Merdeka; literasi digital; media pembelajaran